A new nitrogen rich open chain diazine ligand system: synthesis coordination chemistry and magneto-structural studies. Issue 8 (5th January 2018) - Anwar, Muhammad U.; Al-Harrasi, Ahmed; Gavey, Emma L.; Pilkington, Melanie; Rawson, Jeremy M.; Thompson, Laurence K.
Abstract : A new series of open chain diazine ligands that have a central bipyridne unit with two side-arms offering a range of ketone/alkoxide oxygen donors, diazine and pyridine terminal groups show a strong preference for binding three metals. Abstract : The synthesis and coordination chemistry of a new series of open chain diazine based ligands (L3a H2, L3b H2, andL3c H2 ) is reported. The ligands comprise a central disubstituted bipyridine moiety with two bridging alkoxide oxygen donors, together with diazine and pyridine terminal groups strategically located to coordinate three metal centres. Reactions ofL3a H2 andL3b H2 with CuX2 (X − = ClO4, Cl, NO3 ) yield a trinuclear complex (1 ) and 1-D copper chains (2, 3 ). In these complexes the ligands bind copper ions via Nbipyridne, trans Ndiazine, Ohydrazone, and Npyridne donors while vacant sites are occupied by counter ions or solvent molecules (methanol, water, acetonitrile). Reaction ofL3c H2 with MnCl2 affords a linear trinuclear Mn complex (4 ), where the Mn(ii ) ions are connected via μ2 -Ohydrazone linkers with no N–N bridging. Reaction ofL3a H2 with Fe(SO3 CF3 )2 yields a tetranuclear mixed valence Fe complex (5 ), in which both trans N–N and Ohydrazone bridging is observed. Magnetic studies reveal the presence of moderate to strong antiferromagnetic interactions in complexes1–4 while a mix of ferromagnetic and antiferromagnetic interactions is observed in complex5 .